If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4 + -9) = -26 + 6x Combine like terms: 4 + -9 = -5 7(-5) = -26 + 6x Multiply 7 * -5 -35 = -26 + 6x Solving -35 = -26 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -35 + -6x = -26 + 6x + -6x Combine like terms: 6x + -6x = 0 -35 + -6x = -26 + 0 -35 + -6x = -26 Add '35' to each side of the equation. -35 + 35 + -6x = -26 + 35 Combine like terms: -35 + 35 = 0 0 + -6x = -26 + 35 -6x = -26 + 35 Combine like terms: -26 + 35 = 9 -6x = 9 Divide each side by '-6'. x = -1.5 Simplifying x = -1.5
| 5(x+43)+-2=-2 | | -14+9x=11+8x | | (X*5)-16=3(X+10) | | (4x^2-6x+8)+(7x-3)=0 | | 4.2x-1.5=1.9x+7.7 | | -4(x+12)+9=-7 | | 16*x=64 | | p(x)=x^4-3x^3+18x^2-48x+32 | | -53-7x=55+2x | | 2x-39+-4x=3 | | 4t-5t=3 | | -42+9x=x+86 | | 4x+19=83 | | 5u-6=-21 | | 3(x+41)+8=50 | | 3.8r=-6 | | -29+6x=31+11x | | -2x-47+4x=-21 | | (x+14)(x-2)= | | 10x-45+12x=43 | | 3r(4r-5)=6(5r+8) | | -3y+10x=-5 | | P=11*3 | | -23-3x=-5x+15 | | 8(x+-44)+-6=34 | | -83-12x=7x+183 | | 2(2x-1)-10=-2(1-x) | | -7(x+-37)+-8=-36 | | 2x^2+6xy-9y^2=x+2y | | -63+3x=7x+21 | | 3p^2=3p | | 3(4z-2x)= |